Abdominal X-rays for medical students - Clarke, C. Christopher (Wiley Blackwell, 2015)
Abdominal X-rays for Medical Students is a comprehensive resource offering guidance on reading, presenting and interpreting abdominal radiographs. Suitable for medical students, junior doctors, nurses and trainee radiographers, this brand new title is clearly illustrated using a unique colour overlay system to present the main pathologies and to highlight the abnormalities in abdomen x-rays. Abdominal X-rays for Medical Students: Covers the key knowledge and skills necessary for practical use. Provides an effective and memorable way to analyse and present abdominal radiographs - the unique 'ABCDE' system as developed by the authors Presents each radiograph twice, side by side: the first as seen in the clinical setting, and the second with the pathology clearly highlighted. Includes self-assessment to test knowledge and presentation technique. With a systematic approach covering both the analysis of radiographs and next steps mirroring the clinical setting and context, Abdominal X-rays for Medical Students is a succinct and up-to-date overview of the principles and practice of this important topic.